Risk factors of primary postpartum hemorrhage among postnatal mothers in the public hospital of southern Tigray, Ethiopia, 2019: A case-control study - Muluye, Getachew; Gashaw, Abeba; Woretaw, Lebasie; Girma, Biniam; Tumebo, Tarekegn (Frontiers in Global Women's Health, 2023)
Background Postpartum hemorrhage is the most common direct cause of maternal mortality and morbidity; among them, primary postpartum hemorrhages are an enormous element. Although it has an incredible impact on maternal lifestyle, this is the most neglected area in Ethiopia and there is a lack of studies achieved within the study area. So this study aimed to identify the risk factors of primary postpartum hemorrhage among postnatal mothers in public hospitals in southern Tigray, Ethiopia, 2019. Methods Institution-based unmatched case-control study design was conducted on 318 (106 case and 212 controls) postnatal mothers in public hospitals of Southern Tigray from January to October 2019. We used a pretested, structured interviewer-administered questionnaire and a chart review to collect the data. Bivariate and multivariable logistic regression models were used to identify the risk factors. P-value ≤ 0.05 was considered statically significant for both steps and an odds ratio with a 95% confidence level was used to see the strength of association. Results Abnormal third stage of labor [adjusted odds ratio = 5.86, 95% confidence interval (2.55–13.43), P = 000], cesarean section [adjusted odds ratio = 5.61, 95% confidence interval (2.79–11.30), P = 0.000], lack of active management of third-stage labor [adjusted odds ratio = 3.88; 95% confidence interval (1.29–11.60), P = 0.015], absence of labor monitoring by partograph [adjusted odds ratio = 3.82, 95% confidence interval (1.31–11.09), P = 0.014], lack of antenatal care [adjusted odds ratio = 2.76, 95% confidence interval (1.13–6.75), P = 0.026] and complications during pregnancy [adjusted odds ratio = 2.79, 95% confidence interval (1.34–5.83), P = 0.006] were found to be risk factors for primary postpartum hemorrhage. Conclusion In this study complications and lack of maternal health interventions in the course of the antepartum and the intrapartum period were found to be risk factors for primary postpartum hemorrhage. A strategy for improving essential maternal health services and detecting and handling complications in a timely manner will help to prevent primary postpartum hemorrhage.